URGENSI MANAJEMEN DALAM DAKWAH - Samsinar S (fakultas Ushuluddin dan Dakwah IAIN Bone, 2018)
The implementation of da'wah must be designed and packaged properly so as to produce an effectiveness and efficiency in da'wah. Therefore, there needs to be good management in the process of implementing da'wah starting from planning, organizing, mobilizing, controlling, and evaluating da'wah. The process of implementing da'wah must have a good strategy, method and management in order to produce quality da'wah and achieve the stated preach goals.KeywordsManagement; da’wah